Chemical prospection and biological potential of tropical fruit waste extracts (Research, Society and Development, 2020)
Agro-industries waste from fruits can present a promising source for industrial sectors with the extraction of active principles that have several biological activities. In view of the above, this study aimed to evaluate the biological potential of tropical fruit extracts against antioxidant and amnmicrobial activities. The study evaluated different methods of antioxidant activities (by DPPH and FRAP method), characterization and quantification of phenolic compounds by High Performance Liquid Chromatography (HPLC), antibacterial and antifungal activities of four tropical fruit waste extract. In the extracts were identified several phenolic compounds, the values found were varied from 0.21 to 5.73 mg/L in gallic acid, observing the predominance of gallic acid, catechin, chlorogenic and acid p-coumaric. The antibacterial activity was evaluated by the agar diffusion method using the microorganism Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Salmonella cholerasuis. The antifungal activity was determined by the disc diffusion technique using Aspergillus carbonarius, Aspergillus niger, Aspergillus flavus, Penicillium commune and Penicillium cladosporoides, the extracts showed potential antioxidant activity, antibacterial and antifungal in both tests. The lemon extract showed no inhibition for the fungi.